Draft Annual Plan 1987-88 Vol. IV Statements Uttar Pradesh - Planning Commission (Planning Commission, 1987)
Includes Rs.800 lakh for accelerated programme for development of dacoity prone areas and Rs. 2318 lakh for upgradation of administration under Eighth Finance Commission Award. Includes Rs. 1500 lakh for accelerated programme for development of dacoity prone areas and Rs.5004 lakh for upgradation of administration under Eighth Finance Commission Award. Includes Rs.3800 lakh for accelerated programme for development of dacoity prone areas and Rs. 4032 lakh for upgradation of administration under Eighth Finance Commission Award.
Government of Uttar Pradesh, Planning Department